On Cultivating African Architecture for The Africa, We Need - Kabanda, Patrick (African Journal on Land Policy and Geospatial Sciences, 2022)
Africa’s age-old architectural knowledge is replete with diverse design techniques that satisfy not only aesthetic but also functional purposes. Nevertheless, as is normally the case with many African creative endeavors, this knowledge is not fully harvested. Yet from the COVID-19 pandemic, which demands rethinking of how space is used, to climate change, which questions how structures are designed and made, the need to consider how African architecture can shape the Africa we need, not to mention its contribution to global architecture, is pressing.
Keywords: Architecture, African Architecture, Land usage, Sustainable Architecture, Arts, Culture and Heritage, Natural Synthesis